THE RELATIONSHIP BETWEEN SOIL HEALTH, FLUCTUATIONS OF MICROBIAL POPULATIONS AND MANAGEMENT OF SOIL BORROWED PLANT DISEASES IN AN EPIDEMIOLOGICAL PERSPECTIVE OF PLANT DISEASES: HUBUNGAN ANTARA KESEHATAN TANAH, FLUKTUASI POPULASI MIKROBA DAN MANAJEMEN PENYAKIT TANAMAN YANG TERBAWA TANAH DALAM PRESPEKTIF EPIDEMIOLOGI PENYAKIT TANAMAN - Depriani Gulo, Daria (LPPM UPMI, 2023)
Soil is an important component for the carrying capacity of land for its use by humans. In agriculture, soil is a factor that determines plant growth and yield. This study uses descriptive analysis methods made in literature studies, which use various written sources such as articles, journals and relevant studies that support this research, aiming to find out how diseases attack plants so that they are not able to develop properly. This study concluded that, Soil health is a healthy soil has a good structure, balanced nutrient content and the right acidity level. Microbial populations in soil can experience significant fluctuations due to environmental changes and interactions with plants. Management of soil-borne plant diseases involves using techniques and practices aimed at reducing the risk of plant infection. This includes crop rotation, use of disease-resistant varieties, weed control, sanitation, and proper soil treatment.